Towards effective engagement: a scoping review of strategic communication mechanisms with Indigenous communities - Sarmila Md Sum,; Shahril Mod Husin,; Nurul Darsani Amat Darbis, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Interacting with indigenous people could bring about several challenges due to historical and cultural differences. This research aims to identify and analyse strategic communication mechanisms with indigenous people. It presents a recent review of the communication mechanism used to foster effective engagement between Indigenous people and non-indigenous organizations. Online articles from Google Scholar, Semantic Scholar and UKMLibrary were used. The terms used for reviewing the articles were strategic communication, communication mechanism, indigenous people, and Orang Asli. The scoping review protocol was used for this study. A total of 29 relevant articles published from 2003 to 2023 were filtered and grouped into three major themes for review: cultural sensitivity, community engagement and interpersonal connection. Findings suggested that although previous research had examined the communication mechanism with Indigenous people, there was limited research on communication strategy among different Indigenous communities. While overarching principles exist, each community possesses its own distinct values, languages, and communication preferences. Comprehending these intricacies is crucial for customizing communication techniques successfully. Effective communication with indigenous people necessitates a profound comprehension of cultural, historical, and social settings.